2017
DOI: 10.1063/1.5010982
|View full text |Cite
|
Sign up to set email alerts
|

High-quality multilayer graphene on an insulator formed by diffusion controlled Ni-induced layer exchange

Abstract: The Ni-induced layer-exchange growth of amorphous carbon is a unique method used to fabricate uniform multilayer graphene (MLG) directly on an insulator. To improve the crystal quality of MLG, we prepare AlOx or SiO2 interlayers between amorphous C and Ni layers, which control the extent of diffusion of C atoms into the Ni layer. The growth morphology and Raman spectra observed from MLG formed by layer exchange strongly depend on the material type and thickness of the interlayers; a 1-nm-thick AlOx interlayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…A layer exchange mechanism of this kind was also observed for amorphous carbon/Ni heterostructures. 23 25 Then the graphitic layers are formed at T > 500 °C ( Figure 7 c) according to results observed from XPS measurements. Finally, the graphitic phase concentration increases with the annealing temperature ( T > 700 °C), and its concentration became higher than the concentration of the disordered phase ( Figure 7 d).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…A layer exchange mechanism of this kind was also observed for amorphous carbon/Ni heterostructures. 23 25 Then the graphitic layers are formed at T > 500 °C ( Figure 7 c) according to results observed from XPS measurements. Finally, the graphitic phase concentration increases with the annealing temperature ( T > 700 °C), and its concentration became higher than the concentration of the disordered phase ( Figure 7 d).…”
Section: Resultssupporting
confidence: 64%
“…It was observed that carbon film exchanges with Ni film and graphitizes at elevated temperature. 23 25 Recent theoretical studies explained the graphitization mechanism for RTA: a-C to graphene transformation entails the metal-induced crystallization and layer exchange mechanism. Carbon dissolution in Ni was excluded.…”
Section: Introductionmentioning
confidence: 99%
“…For the samples with the IL, the I G / I D ratio is as low as for the samples without the IL for t ≤ 20 nm, while it dramatically increases for t ≥ 50 nm and exceeds 20. The crystal quality of the MLG, estimated from the I G / I D ratio, likely reflects the contamination from the substrate and the grain size enlargement by inserting the IL 42 . Although the I G / I D ratio of 20 is still lower than that of MLG formed by the transfer technique or high-temperature CVD 4 , this value is the highest among MLG synthesized on insulators by metal-induced solid-phase crystallization 18,19,23,25 .
Figure 2Raman study of MLG formed by layer exchange.
…”
Section: Resultsmentioning
confidence: 99%
“…AA and AB stacking) 44,45 . Unfortunately, because the current MLG is small-grained polycrystalline where the grains are randomly oriented in the in-plane direction 42 , it is difficult to identify the stacking.
Figure 3Characterization of the cross-section of the sample for t = 10 nm without the IL before Ni removal. ( a ) Bright-field TEM image.
…”
Section: Resultsmentioning
confidence: 99%
“…The chemical vapor deposition (CVD) method using metal catalysis with high carbon solubility are commonly utilized for the synthesis of the multilayer graphene. In the liquid–solid growth process, the graphene layers are easily rotated in the liquid phase of metal catalysis.…”
Section: Introductionmentioning
confidence: 99%